Melodrama Made Good: Ennoblement by Deletion in Edgar Stillman Kelley’s Score to Ben-Hur - Hannington, Luke (Journal of Film Music, 2013)
As one of the last great stage melodramas, Edgar Stillman Kelley’s Score to Ben-Hur represents one of the last flourishes of melodramatic music before the onset of the movie age. This article provides an overview of the music in the autograph score of Ben-Hur and explores the various dramatic functions of the music as presented by Kelley.